Histosols in an Upper Montane Environment in the Itatiaia Plateau - Soares,Paula Fernanda Chaves (2016)
ABSTRACT: Highland environments favor accumulation and preservation of soil organic matter (SOM) due to low temperatures, leading to the formation of Histosols. The Itatiaia National Park (INP), Rio de Janeiro, Brazil, offers conditions for preservation of SOM deposited over time, which has led to the formation of these soils. The objective of this study was to characterize Histosols in this environment, with the premise that it may provide evidence of changes in vegetation. Organossolos (Histosols) were sampled, characterized, described, and analyzed for their properties, stable isotopes of 12C and 13 14 15 14 C, N and N, and dating of organic matter through C. The soils were classified in the Brazilian Soil Classification System as Organossolo Háplico Hêmico típico - RJ-01 (Haplohemists) and Organossolo Fólico Sáprico cambissólico - RJ-02 (Udifolists). The morphological properties, degree of transformation, and chemical fractioning of SOM were consistent with hemic and sapric materials. The δ13C and δ15N isotopic analyses showed a difference in the contribution of plant materials. In RJ-01, there was previous influence of algae, due to poor drainage, and depletion of δ13C, suggesting a mix of C3 and C4 plants. RJ-02 showed influence of C3 type plants. The 14C dating for RJ-01 was 3280±80 years, and for RJ-02, 2005±5 years (modern age).